Magnetic resonance imaging to determine the incidence of brain ischaemia in patients with β-thalassaemia intermedia - Karimi, Mehran; Bagheri, Hadi; Rastgu, Fatemeh; Rachmilewitz, Eliezer A. (Thrombosis and Haemostasis, 2010)
One complication in patients with β-thalassaemia who had prolonged survival is chronic hypercoagulable state, which results in thromboembolic events involving major organs including the brain. We determined the prevalence of microthrombosis in the brain in an asymptomatic subgroup of patients with β-thalassaemia intermedia (TI) who had undergone splenectomy. This retrospective review included 200 patients with TI diagnosed on the basis of blood count, haemoglobin (Hb) electrophoresis and clinical data. Their ages ranged from 18 to 34 years, 19 (63.3%) were women and 11 (36.7%) were men. We selected 30 patients at random who fulfilled the inclusion criteria: Hb concentration >7 g/dl), splenectomy and platelet count >500,000/ml. Their mean Hb concentration was 8.4 g/dl and their mean ferritin concentration was 519 ng/ml. Magnetic resonance imaging (MRI) was done in every patient, and the findings were interpreted by an expert neuroradiologist. Imaging studies showed pathological findings in 28% of the patients. Six had changes in the white matter suggestive of ischaemia and two had evidence of small infarctions. Conclusion: 1) In this small subset of patients diagnostic magnetic resonance imaging to monitor early asymptomatic or subclinical vascular damage in the brain can be considered when they reach the age of 20 years, and repeated every 3–5 years. 2) Treatment with antiplatelet aggregants is suggested in patients with documented asymptomatic brain ischaemia. 3) These results require confirmation in a larger group of similar patients with other types of thalassaemia who are multitransfused or have an intact spleen.
Keywords: β-thalassaemia intermedia; magnetic resonance imaging; brain ischaemia